Yogurt's flexible image during its rise in popularity in post-war Belgium. (1st January 2017) - Verriet, Jon; Leroy, Frédéric
Abstract: The consumption of yogurt in Western countries has risen for over a century, first slowly, then more rapidly. The purpose of the present study was to investigate this prolonged phase of growth, by examining the popularity and the projected image of yogurt. A particular focus was on the way these aspects were reflected in consumption patterns and media representations. The data showed how during its period of rapid popularization, yogurt's visibility in the media greatly increased. It was concluded that the product's image was highly flexible in post-war decades, evidenced by the multi-pronged approach taken by marketers. Yogurt was not only advertised as both tasty and healthy, but also as natural and convenient, a strategy that appears to have been informed by consumers' preferences and existing cultural values. This demonstrates how a high degree of product differentiation and diversification during a product's growth stage can result in a heterogeneous image, allowing for a broad range of marketing strategies.